MEKANISME PENYELESAIAN SENGKETA GATT DAN WTO DITINJAU DARI SEGI HUKUM PENYELESAIAN SENGKETA INTERNASIONAL - Lona Puspita (Fakultas Hukum Universitas Tamansiswa Padang, 2018)
The development of science and technology and the pattern of community activities in the world increasingly touch each other, need each other and determine each other destiny, but also compete with each other, especially in trade. With the establishment of an international trade organization or WTO increasingly eliminates the boundaries between countries. Therefore many cause problems in the implementation of inter-state trade agreements. This research uses normative legal research with primary data source that is secondary data. The research finds that international dispute resolution mechanism is one of the mechanisms of supervision in international law. While the relation between GATT and WTO dispute settlement method with international dispute settlement that is both can be done judicially and non-judicially.